2007
DOI: 10.1038/sj.ejcn.1602617
|View full text |Cite
|
Sign up to set email alerts
|

A valid semiquantitative food frequency questionnaire to measure fish consumption

Abstract: Objective: To validate a detailed semiquantitative food frequency questionnaire designed to measure habitual fish and seafood consumption. Design: Cross-sectional validation study using an independent biomarker of fish consumption. Setting: Perth metropolitan area, Western Australia. Subjects: Ninety-one healthy volunteers of both sexes aged 21-75 years. Methods: Participants completed the questionnaire and provided a fasting blood sample for erythrocyte membrane omega-3 fatty acid (eicosapentaenoic acid (EPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 31 publications
(54 reference statements)
3
34
0
1
Order By: Relevance
“…The percentage of DHA in erythrocyte membranes is quantitatively much larger than EPA, and during pregnancy the conversion of EPA to DHA is given priority (39) . The present study is in accordance with previous studies in that the relationship between fish consumption and serum/tissue DHA applies primarily to intake of fatty fish and n-3 supplements (34,40,41) . When total intake of milk and other dairy products, containing iodine from mandatory fodder fortification (14,42) , was included as a covariate, no fish variables were significantly associated with urinary iodine excretion (43) .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The percentage of DHA in erythrocyte membranes is quantitatively much larger than EPA, and during pregnancy the conversion of EPA to DHA is given priority (39) . The present study is in accordance with previous studies in that the relationship between fish consumption and serum/tissue DHA applies primarily to intake of fatty fish and n-3 supplements (34,40,41) . When total intake of milk and other dairy products, containing iodine from mandatory fodder fortification (14,42) , was included as a covariate, no fish variables were significantly associated with urinary iodine excretion (43) .…”
Section: Discussionsupporting
confidence: 82%
“…During pregnancy, there is a faster turnover of fat storage that may modify the profile of erythrocyte n-3 fatty acids and lower the correlation between dietary intake and erythrocyte n-3 fatty acids (31) . It has been suggested that EPA is under different homeostatic and metabolic control than DHA (34) . The percentage of DHA in erythrocyte membranes is quantitatively much larger than EPA, and during pregnancy the conversion of EPA to DHA is given priority (39) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data collected on 109 participants as part of an Australianbased study to validate a thorough FFQ on fish con-sumption were used 5 . Healthy (defined as no history of heart disease, cancer (not including skin cancer), severe inflammatory diseases, emphysema or asthma, diabetes, severe gastrointestinal disease or mental illness) volunteers aged 21-75 years from the Perth metropolitan area were recruited to complete the developed FFQ and provide a fasting blood sample for analysis of omega-3 polyunsaturated fatty acids (PUFA), between March and November 2005.…”
Section: Recruitmentmentioning
confidence: 99%